Lord Byron - Graham, Peter W. 1951- (Twayne Publ., 1998)
Situates the 19th-century author-icon and his literary achievements in various contexts. A concise biography considers all of Byron's major poems grouped according to literary kind or genre. Separate chapters are devoted to Byron's accomplishments as lyricist, satirist, tale - teller, dramatist, and contriver of the narratives "Childe Harold" and "Don Juan". For general readers and specialists.
Keywords: Byron, George Gordon Byron <Baron, 1788-1824>; Byron, George Gordon Byron <Baron, 1788-1824> - Criticism and interpretation; Byron, George Gordon Byron -- Baron -- 1788-1824